AB214. SOH26AB_0407. Intracorporeal vs. extracorporeal anastomosis in oncologic resections: trends and outcomes - Khan, Muhammad Hadi; Suliman, Eman; Khattak, Arshia; Kashif, Bilal; Khattak, Abid; Paul, Sharjeel; Mustafa, Hamid (Mesentery and Peritoneum, 2026)
Delayed gastrointestinal (GI) recovery remains a major contributor to morbidity and prolonged hospitalisation following oncologic colectomies. Intracorporeal anastomosis (ICA) has been proposed to improve bowel function compared with extracorporeal anastomosis (ECA); however, the impact of anastomotic technique and configuration on clinical outcomes remains incompletely defined. We aimed to address this deficit in the literature.